2019
DOI: 10.3389/fonc.2019.01126
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Controversial Issues in the Management of Head and Neck Cancer: A Swiss Multidisciplinary and Multi-Institutional Patterns of Care Study—Part 2 (Radiation Oncology)

Abstract: Background: The Head and Neck Cancer Working Group of Swiss Group for Clinical Cancer Research (SAKK) has investigated the level of consensus (LOC) and discrepancy in everyday practice of diagnosis and treatment in head and neck cancer.Materials and Methods: An online survey was iteratively generated with 10 Swiss university and teaching hospitals. LOC below 50% was defined as no agreement, while higher LOC were arbitrarily categorized as low (51–74%), moderate (75–84%), and high (≥85%).Results: Any LOC was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
(97 reference statements)
0
2
0
Order By: Relevance
“…They reported an overall rate of occult metastasis of 23%. Similarly, we evaluated the incidence of occult additional metastasis in the rcN+ neck by compartmentalization of the neck in its levels, which is especially useful for the planning of adjuvant salvage radiotherapy 14 . Occult additional metastases in radiologically uninvolved neck levels were observed in 25% of the patients treated with salvage neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…They reported an overall rate of occult metastasis of 23%. Similarly, we evaluated the incidence of occult additional metastasis in the rcN+ neck by compartmentalization of the neck in its levels, which is especially useful for the planning of adjuvant salvage radiotherapy 14 . Occult additional metastases in radiologically uninvolved neck levels were observed in 25% of the patients treated with salvage neck dissection.…”
Section: Discussionmentioning
confidence: 99%
“…Another compartmentalization strategy for HNSCC is the omission of the primary tumor bed for patients with a favorable local risk profile that receive PORT to the at-risk areas in the involved neck. Why the postoperative primary tumor bed should be irradiated in the presence of multiple nodal positivity and/or ECE, whereas the same tumor bed would not receive any radiation if the neck is pN0-1 lacks a logical rationale ( 27 ). A national patterns of care study revealed no consensus on this issue with 70% of the centers not separating the tumor bed from the dissected nodal levels, and 30% allowing for this type of de-escalation ( 27 ).…”
Section: Discussionmentioning
confidence: 99%